Effectiveness of a new thermal insulation blanket in the control of inadvertent perioperative hypothermia and comfort: a randomized controlled trial - Isaura Carvalho; Miguel Carvalho; Fernando Abelha; Teresa Martins (BMC Anesthesiology)
Abstract Background Disturbances in the thermoregulatory system can precipitate inadvertent hypothermia in patients undergoing surgeries lasting over 60 min, causing serious complications in the recovery process. Cutaneous thermal protection is relevant for the control of temperature of patients in the perioperative setting. The standard thermal protection widely utilized is an electric forced warm air blanket. This study compared a new layered textile blanket with the standard protection. The hypothesis posited that the textile blanket could provide cutaneous thermal protection comparable to that of the standard protection (forced-air warming blanket), in terms of temperature variation and safety. Methods This randomized controlled trial was conducted at a Portuguese orthopedic hospital from October 2018 to January 2019, comprising 124 adult patients undergoing elective total knee arthroplasty. Participants were randomly allocated to either the intervention group, receiving the textile blanket, or to the control group, receiving standard measures. Tympanic temperature, shivering, and thermal comfort perception were evaluated at six time points. Comfort dimensions and ergonomic aspects were also assessed. Parametric statistics were performed, and independent samples t-tests and repeated measures were used to compare temperature variations and thermal comfort. Results No statistically significant differences were found between groups in mean temperature variation, visual perception of thermal comfort, and thermal and perioperative comfort scales. The intervention group (n = 65) scored significantly higher in ergonomic evaluations compared to the control group (n = 59) for: fit to body and general comfort (p = 0.004), touch (p = 0.005), and feeling of comfort with the inner layer texture and shape (p < 0.001). Conclusion The tested blanket had a comparable performance to the standard protection, suggesting it as a potential sustainable alternative to the recommended measures for thermal protection. However, further investigations across diverse contexts and populations are needed to validate these findings.